The Effect of Parking Waiting Time, OTP and Incoming Baggage Handling System (BHS) on Passenger Satisfaction with Service Quality as A Mediation Variable at Terminal 3 Soekarno-Hatta International Airport - Idham Iriansyah; Jermanto Setia Kurniawan; Yana Tatiana; Mustika Sari; Reni D. Octaviani (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyze the influence of Parking Stand, On-Time Performance (OTP), and Inbound Baggage Handling System (BHS) Waiting Time on Passenger Satisfaction, with Service Quality as the mediating variable at Terminal 3 of Soekarno-Hatta International Airport. The population of this study consists of passengers at Terminal 3 of Soekarno-Hatta International Airport, with a sample of 168 respondents meeting the criteria, using a quantitative descriptive approach. The research method employed is the Structural Equation Model (SEM), analyzed using Smart-PLS 3.2.9 software. The results indicate significant effects of Parking Stand on passenger satisfaction, On-Time Performance on passenger satisfaction, BHS Waiting Time on passenger satisfaction, Parking Stand on service quality, On-Time Performance on service quality, BHS Waiting Time on service quality, and Service Quality on passenger satisfaction. However, Parking Stand has an insignificant effect on service quality. Furthermore, Service Quality mediates the relationship between Parking Stand and passenger satisfaction, as well as between On-Time Performance and passenger satisfaction. However, Service Quality does not mediate the relationship between BHS Waiting Time and passenger satisfaction.